The Importance Of Teacher Pedagogical Skills In The Innovative And Integrative Organization Of Primary Education (Eurasian Journal of Learning and Academic Teaching, 2023)
This article will talk about the importance of pedagogical skills in the teacher in the innovative and integrative Organization of primary education. A number of opinions are also cited from the literature on the subject. After all, in today's globalization process, the innovative and integrative Organization of education, especially primary education, is one of the important tasks facing any educator. Pedagogical skill, on the other hand, is a key factor in each educator leading the children of the land to the path of development. The paper also includes research Objects, research methods, and conclusions and suggestions.